2013
DOI: 10.2146/ajhp120253
|View full text |Cite
|
Sign up to set email alerts
|

Vandetanib: A novel targeted therapy for the treatment of metastatic or locally advanced medullary thyroid cancer

Abstract: Vandetanib has been shown to be more effective than placebo in the treatment of advanced MTC; however, it has not been compared with radiation, resection, or embolization. Vandetanib also has significant and fairly common cardiac toxicities. The cost, benefits, and risks of vandetanib for patients with MTC should be weighed, as alternative treatments remain an option for most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Axitinib was associated with a higher risk of hypertension event than sunitinib (Baek et al 2019). And vandetanib's higher cardiac toxicity (Ton et al 2013). Furthermore, this NMA provided the ranking possibility to induce cardiovascular damage (all grades) of nine commonly used VEGFR-TKIs', severe cardiovascular event (Grade 3 or higher), hypertension, serious hypertension (Grade 3 or higher) and cardiac event risk.…”
Section: The Strengths Of Our Network Meta-analysismentioning
confidence: 96%
“…Axitinib was associated with a higher risk of hypertension event than sunitinib (Baek et al 2019). And vandetanib's higher cardiac toxicity (Ton et al 2013). Furthermore, this NMA provided the ranking possibility to induce cardiovascular damage (all grades) of nine commonly used VEGFR-TKIs', severe cardiovascular event (Grade 3 or higher), hypertension, serious hypertension (Grade 3 or higher) and cardiac event risk.…”
Section: The Strengths Of Our Network Meta-analysismentioning
confidence: 96%
“…Furthermore, dual inhibition of VEGFR and EGFR using vandetanib (ZD6474) resulted in significant tumour growth inhibition in a range of histologically diverse human xenograft models (Wedge et al ., ; Holden et al ., ; Yoshikawa et al ., ). When moved for clinical development, vandetanib demonstrated a high therapeutic efficacy in phases I–III trials against metastatic medullary thyroid cancer, which lead eventually to FDA approval (Leboulleux et al ., ; Wells et al ., ; Ton et al ., ). However, in many other clinical trials, vandetanib showed either acceptable clinical activities along with safety concerns or limited clinical activities that warrant pre‐selection of patients (Blackhall et al ., ; Hsu et al ., ; Kreisl et al ., ; Lee et al ., ; Meyerhardt et al ., ).…”
Section: Mechanisms Of Enhanced Therapeutic Efficacymentioning
confidence: 97%
“…Vandetanib (VTB) is a MTKi targeting both VEGFR and EGFR, approved for the treatment of advanced medullary thyroid cancer 28 - 31 . It binds covalently to the cysteine residues of the TK domain and prevents binding of ATP, phosphorylation of the TK dimer and initiation of subsequent downstream signalling pathways.…”
Section: Introductionmentioning
confidence: 99%